LiFi- Future Technology - Smys, S.; Raj, Jennifer S. (Journal of Ubiquitous Computing and Communication Technologies, 2022)
The introduction of Wi-Fi into the residences is creating a biological havoc among humans. A lot of research has been evolved and presented depicting the various imperfections caused by the radiation of Wi-Fi. To overcome this LiFi technology may be used for indoor communication instead of Wi-Fi. LiFi communication needs line of sight for communication. LiFi transfers the information through visible light. Light cannot travel through opaque objects. The various properties of light like Reflection, Refraction, scattering effects on visible light will lead to data loss. Hence LiFi is preferably used indoors. This article discusses on the effects of biological degradation caused by Wi-Fi, Bluetooth etc. in short, this article enlists the effects of radio waves in accordance with the psychological changes caused in mankind. This in turn will lead to build a system which will also ensure the safety of the ecosystem for the development of mankind.